Harlan miners speak : report on terrorism in the Kentucky coal fields - Dreiser, Theodore, 1871-1945 (The University Press of Kentucky, 2015)
The Dreiser Committee, including writers Theodore Dreiser, John Dos Passos, and Sherwood Anderson, investigated the desperate situation of striking Kentucky miners in November 1931. When the Communist-led National Miners Union competed against the more conservative United Mine Workers of America for greater union membership, class resentment turned to warfare. Harlan Miners Speak, originally published in 1932, is an invaluable record that illustrates the living and working conditions of the miners during the 1930s. This edition of Harlan Miners Speak, with a new introduction by noted historian.